2009
DOI: 10.1007/s12010-009-8686-9
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Penicillin G Acylase Immobilization Using Highly Porous Cellulose-Based Polymeric Membrane

Abstract: The different ionic molecules/compounds were used as a ligand for the immobilization of penicillin G acylase on the highly porous cellulose-based polymeric membrane having buffer flux 1,746 LMH (L m(-2) h(-1)) at 0.5 bar pressure. The immobilized enzyme activity around 250 U(App) was obtained with the ligand such as proline, tryptophan, casein acid hydrolysate, and brilliant green. Comparatively, proline showed less IMY% (percentage immobilization yield--58) but higher RTA% (percentage of activity retention--7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…67 Cibacron Blue F3GA, Brilliant green and Procion red are some dyes that have been successfully incorporated in membranes. [68][69][70][71] These dyes can easily be incorporated in cellulose based membranes due to the hydroxyl groups present in cellulose. 67 These hydroxyl groups interact with the chloride or fluoride atoms present on the triazinyl groups in the dyes.…”
Section: Enzyme Immobilization Techniques/chemistries On Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Cibacron Blue F3GA, Brilliant green and Procion red are some dyes that have been successfully incorporated in membranes. [68][69][70][71] These dyes can easily be incorporated in cellulose based membranes due to the hydroxyl groups present in cellulose. 67 These hydroxyl groups interact with the chloride or fluoride atoms present on the triazinyl groups in the dyes.…”
Section: Enzyme Immobilization Techniques/chemistries On Membranesmentioning
confidence: 99%
“…This, however, is not a general practice as revealed by Table 3. 69 Entrapment of enzymes into membranes. Entrapment of enzymes has the advantage of wider applicability to many enzymes and relatively small changes in enzyme structure and function after immobilization.…”
Section: Enzyme Immobilization Techniques/chemistries On Membranesmentioning
confidence: 99%
“…6. The immobilized PGA retained over 70 % residual activity after being used 10 times, which was larger than that of penicillin G acylase on magnetic Fe 3 O 4 nanoparticles modified by ionic liquids 19 , and basically reached the level of penicillin G acylase on aldehyde-functionalized mesoporous silica-Fe 3 O 4 nanocomposites 20 . The high recycle relative activity revealed that the reusability of the immobilized PGA was better than that of free PGA.…”
Section: Reusability Of Immobilized Pgamentioning
confidence: 95%
“…Organic carriers include natural polymers and synthetic polymers. Natural macromolecule carriers mainly include cellulose, dextran, agarose, and chitosan and so on . Because of their wide sources, pollution‐free, renewability, and other advantages, they have attracted the attention of researchers.…”
Section: Immobilization Pgamentioning
confidence: 99%